Biguanides in combination with olaparib limits tumorigenesis of drug‐resistant ovarian cancer cells through inhibition of Snail. (21st December 2019) - Wang, Qiong; López‐Ozuna, Vanessa M.; Baloch, Tahira; Bithras, Joanne; Amin, Oreekha; Kessous, Roy; Kogan, Liron; Laskov, Ido; Yasmeen, Amber
Abstract: Ovarian cancer is the most lethal gynecological malignancy. Currently, new chemotherapeutic strategies are required to improve patient outcome and survival. Biguanides, classic anti‐diabetic drugs, have gained importance for theiri antitumor potency demonstrated by various studies. Olaparib is a PARP inhibitor approved for maintenance therapy following platinum‐based chemotherapy. Furthermore, Snai1, a transcription factor that works as a master regulator of the epithelial/mesenchymal transition process (EMT) is involved in ovarian cancer resistance and progression. Here we aimed to demonstrate the possible cross talk between biguanides and Snail in response to olaparib combination therapy. In this study, we have shown that while in A2780CR cells biguanides reduced cell survival (single treatments ~20%; combined treatment ~44%) and cell migration (single treatments ~45%; biguanide‐olaparib ~80%) significantly, A2780PAR exhibited superior efficacy with single (~60%) and combined treatments (~80%). Moreover, our results indicate that knock‐down of Snail further enhances the attenuation of migration, inhibits EMT related‐proteins (~90%) and induces a synergistic effect in biguanide‐olaparib treatment. Altogether, this work suggests a novel treatment strategy against drug‐resistant or recurrent ovarian cancer. Abstract : Biguanides in combination with PARP inhibitors synergistically reduce EMT, proliferation and survival of ovarian drug‐resistant cancer cells.